Cytotoxic and Antiproliferative Properties of Metabolites Produced by Six Strains of Lactobacillus Plantarum on Human Cancer Cells - Chuah, Li Oon (2010)
Whole cells, cytoplasmic fractions and fermented products of LAB have been tested for anticancer effect. However, limited information is available for the metabolites produced by Lactobacillus plantarum. In this study, the anticancer effect of metabolites produced by six strains of L. plantarum (UL4, TL1, RS5, RG14, RG11 and RI11) isolated from Malaysian fermented foods was evaluated. All metabolites exhibited in vitro cytotoxic effect on the tested cancer cells (breast, colorectal, cervical, liver and leukemia cancer cell lines). An increased cytotoxic effect was observed with increased dose of metabolites used and time of incubation. In particular, metabolites UL4 exerted the most potent cytotoxicity against human breast carcinoma cells MCF-7 in a dose- and time-dependent manner in MTT assay, with inhibition concentration of 50 % growth (IC50) value of 15, 12 and 10% (v/v) for 24, 48 and 72 hours of incubation, respectively. In contrast, no cytotoxicity was detected in primary human peripheral blood mononuclear cells, mouse splenocytes, thymocytes and bone marrow cells for all the six metabolites tested. However, limited cytotoxicity was detected in nonmalignant human glandular epithelium cells MCF-10A when treated with UL4 and RG14 metabolites. Additionally, UL4 metabolites did not cause haemolysis, indicating cytotoxic effect of metabolites of six strains of L. plantarum is selective for malignant cells but spared on normal cells. Antiproliferative effect was focused on MCF-7 and colon cancer cell line (HT-29). In BrdU cell proliferation assay, all tested metabolites inhibited DNA synthesis of MCF-7 and HT-29 cells. An increased antiproliferative effect was observed with increased dose of metabolites used and time of incubation. In particular, UL4 metabolites exhibited 100% proliferation inhibition on MCF-7, whereas RG14 metabolites exhibited 89% proliferation inhibition on HT-29 for 72 hours of incubation. Growth arrest study showed significant cell growth inhibition (P < 0.05) in MCF-7 treated with UL4 metabolites and HT-29 cells treated with RG14 metabolites. Mode of cell death induced by UL4 metabolites on MCF-7 cells was elucidated. Results obtained in trypan blue dye exclusion assay suggested that UL4 metabolites did not cause necrosis. Induction of apoptosis rather than necrosis by UL4 metabolites was evident by the presence of most characteristics of apoptosis such as cell shrinkage, blebbing of cell membrane and fragmentation of DNA and nucleus. Annexin V/PI staining showed that substantial early apoptotic cells were detected in MCF-7 cells treated with UL4 metabolites compared to untreated control group. Cells treated with UL4 metabolites showed growth arrest at G0/G1 cell phase at 24 hours, followed by the increment of cells in sub-G0/G1 in DNA cell cycle analysis. In addition, the TUNEL assay showed that remarkable TUNEL-positive cells were detected in UL4 metabolites-treated MCF-7 cells. The results obtained in this study indicate the potential use of LAB metabolites as a promising antiproliferative and apoptosis induction agent as an alternative in nutraceutical industry and cancer therapy.